2018
DOI: 10.1103/physrevb.98.024501
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Tc by symmetry principles: The concept of superconducting fitness

Abstract: We propose a generalization of the concept of superconducting fitness, which allows us to make statements analogous to Anderson's theorems concerning the stability of different superconducting states. This concept can be applied to complex materials with several orbital, layer, sublattice or valley degrees of freedom. The superconducting fitness parameters FA(k) and FC (k) give a direct measure of the robustness of the weak coupling instability and of the presence of detrimental terms in the Hamiltonian, respe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 42 publications
6
69
0
Order By: Relevance
“…If the system under consideration is translation invariant we can Fourier‐transform from real‐space to momentum space and we find the following condition for odd‐ω pairing: trueĥboldktrueΔ̂boldktrueΔ̂boldktrueĥk0This condition is in fact identical to a measure of “superconducting fitness” recently discussed by Ramires and Sigrist . In that work, it was demonstrated that whenever this quantity is non‐zero there is a reduction in the critical temperature.…”
Section: General Results For Multiband Odd‐frequency Pairingmentioning
confidence: 54%
See 3 more Smart Citations
“…If the system under consideration is translation invariant we can Fourier‐transform from real‐space to momentum space and we find the following condition for odd‐ω pairing: trueĥboldktrueΔ̂boldktrueΔ̂boldktrueĥk0This condition is in fact identical to a measure of “superconducting fitness” recently discussed by Ramires and Sigrist . In that work, it was demonstrated that whenever this quantity is non‐zero there is a reduction in the critical temperature.…”
Section: General Results For Multiband Odd‐frequency Pairingmentioning
confidence: 54%
“…In that work, it was demonstrated that whenever this quantity is non‐zero there is a reduction in the critical temperature. The authors, therefore, concluded that superconducting fitness can be a tool in the search for order parameters that are expected to be more thermodynamically stable . It is here interesting to note that, just one year prior to the publication of ref.…”
Section: General Results For Multiband Odd‐frequency Pairingmentioning
confidence: 88%
See 2 more Smart Citations
“…This property also holds exactly for all realizations of the idealized system but may not hold for real nafen. The unexpected reaction of some superconductors on addition of impurities was recently discussed in connection with multi-orbital superconductors [17,18,19]. The superfluid 3 He falls in this category.…”
Section: Discussionmentioning
confidence: 96%